Predicting Coulomb explosion fragment angular distributions using molecular ground-state vibrational motion. Issue 19 (6th May 2022) - Minion, Louis; Lee, Jason W. L.; Burt, Michael
Abstract : The outcomes of laser-induced Coulomb explosions can be predicted and matched to experiments using the computed vibrational motion of a target molecule. Abstract : Laser-induced Coulomb explosions can be used to identify gas-phase molecular structures through correlations between fragment ion trajectories. This report presents a model for predicting these outcomes, which first establishes the neutral equilibrium geometry of a target molecule using electronic structure calculations, and then samples a probability distribution of potential ground-state configurations by allowing for zero-point vibrational motion. Candidate structures are assumed to explode instantaneously into charged fragments, and the simulated ion trajectories are correlated using recoil-frame covariance analysis. The effects of detection efficiency and fluctuating experimental conditions are also considered. The results were found to match experimental data, indicating that Coulomb explosion fragment angular distributions produced from highly-charged ions depend largely on the internal motion of the target molecule.